A Learning Development Of Beauty Skill Program At A Vocational School In Preserving Local Wisdom - Otin Martini, Engkus Kuswarno; Engkus Kuswarno; M. Andriana Gaffar; Rianti Cahyani (JTP - Jurnal Teknologi Pendidikan, 2021)
A Learning Development Of Beauty Skill Program At A Vocational School In Preserving Local Wisdom. Objectives: The research is to analyze the learning development of beauty skill program at a vocational school in preserving local wisdom. Methods: to employ a qualitative approach with an analytically descriptive method towards two-state vocational schools in Kabupaten Bandung and Bandung city. Library research, in-depth interviews, a document study and observation were carried out to gather data. Informants were chosen by using a snowball technique, the findings, then, were examined and analyzed by using management theory by Deming, curriculum theory of social reconstruction and learning theory of constructivism by Vygotsky. Findings: Learning development planning of beauty skill at a vocation school in preserving local wisdom is designed by formulating vision and mission, arranging curriculum, providing more productive teachers and improving learning facilities. Learning development implementation is made by achieving student’s competence, involving experts and industrial and business world. Learning development is supervised by the Department of Education, Branch Department of Education West Java Provincial Government and school superintendent. The problem faced in learning development is the lack of productive subject time allotment, human resources and qualified teachers understanding local wisdom. The improvement is by enhancing industrial and business world cooperation and teaching factory, collaborating with professional, experts and practitioner organization, using subject time allotment and extracurricular activities. Conclusion: By learning development of beauty skill program in preserving local wisdom, it affects the quality improvement of graduates who have high awareness towards local wisdom, educational service improvement and the achievement of learning development implementation and the learning quality improvement.